Antecedents and preventions of problematic internet use: A systematic literature review - Anis Aniza, Awi; Puteri Fadzline, Muhamad Tamyez; Nurhaizan, Mohd Zainudin; Siti Aisyah, Panatik (Atlantis Press, 2021)
The aim of this systematic literature review is to map the investigation in the subject of Problematic Internet Use (PIU) focuses on Evidences as well as Global Lessons. Further, this particular analysis endeavours to review the substantial facts and lessons used in PIU research and to estimate the severity of problems that persist when an individual uses the internet excessively. This review was guided and consistently compiled using PRISMA which is considered a rigorous method for conducting a literature review. Furthermore, the technique has a number of distinct unique advantages. Besides that, the authors have started the process by providing the full text of all related articles from the search engine. All articles next will be reviewed after full-text reading to ensure the suitability of focus literature. The initial search yielded 307 results. Following a thorough inspection of the articles’ titles and abstracts, the articles that did not meet the inclusion criteria were excluded. In a total of 62 studies, trends in the study of all age levels as well as children, adolescent/emergent and adult PIU were discovered. These trends were conceptualized into specific, activity-related and contextual elements. Findings suggested that sociodemographic and psychosocial factors are actually likely the most explored that have demonstrated considerable relationships with PIU. While, more research focuses on activity- related factors are required in order to accomplish a clearer in terms of understanding the PIU behaviours and to incorporate into an extensive model which will guide future research in this growing industry.